Unpacking global research on academic resilience in school education: a bibliometric mapping and systematic review - I Putu Agus Apriliana; Damianus Dao Samo; Rizki Novirson (Psikopedagogia, 2025)
Academic resilience has emerged as a critical construct for understanding how students adapt to challenges across diverse educational contexts. Despite its growing prominence, the conceptual structure and developmental trajectory of resilience among school-aged learners remain insufficiently mapped. This study aims to (1) map global publication and authorship trends, (2) identify dominant theme patterns, (3) examine target populations and methodological approaches, and (4) synthesize reported outcomes and research outputs. Screening 1,226 reputable-index documents yielded 993 articles for bibliometric analysis, from which a subset of 48 peer-reviewed journal articles published between January 2015 and October 2025 was systematically reviewed. Bibliometric findings indicate sharp growth after 2018, with dominant contributions from the United States and China, alongside widening participation from Europe and the Asia-Pacific region (e.g., Indonesia). These findings also identify highly cited works that have shaped the field, as well as five dominant thematic clusters spanning socio-demographic, educational, psychosocial, health-related, and methodological dimensions. Content analysis reveals a focus on adolescents, a predominance of quantitative methods, and outcomes across academic, psychological, motivational, and relational domains. In contrast, experimental, intervention, and qualitative studies point to gaps in early education, systemic equity, and context-sensitive applications. In conclusion, this review demonstrates the field's maturation and diversification while underscoring the need for more intervention-based, longitudinal, and context-sensitive studies, particularly in underrepresented primary education settings. These findings also highlight the importance of school counseling in implementing evidence-based, context-sensitive resilience interventions, alongside systematic evaluation to promote sustainable student outcomes.